2020
DOI: 10.1101/2020.04.17.20061440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Presence of SARS-CoV-2-reactive T cells in COVID-19 patients and healthy donors

Abstract: 42 Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a rapidly 43 unfolding pandemic, overwhelming health care systems worldwide 1 . Clinical manifestations of 44 Coronavirus-disease 2019 (COVID-19) vary broadly, ranging from asymptomatic infection to 45 acute respiratory failure and death 2 , yet the underlying mechanisms for this high variability are 46 still unknown. Similarly, the role of host immune responses in viral clearance of COVID-19 47 remains unresolved. For SARS-CoV (2002/03… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
237
1
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(286 citation statements)
references
References 36 publications
33
237
1
15
Order By: Relevance
“…At autopsy, patients who succumbed to infection all had high virus levels in the respiratory tract and other tissues (49), suggesting an ineffective, underdeveloped, or off-target immune response. Nevertheless, nonhospitalized subjects who recovered from COVID-19 had evidence of T cell memory to the virus (50). SARS-CoV2 specific antibodies are also found in convalescent subjects and patients are currently being treated with convalescent plasma therapy (28,51).…”
Section: Discussionmentioning
confidence: 99%
“…At autopsy, patients who succumbed to infection all had high virus levels in the respiratory tract and other tissues (49), suggesting an ineffective, underdeveloped, or off-target immune response. Nevertheless, nonhospitalized subjects who recovered from COVID-19 had evidence of T cell memory to the virus (50). SARS-CoV2 specific antibodies are also found in convalescent subjects and patients are currently being treated with convalescent plasma therapy (28,51).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, when we first obtained the dataset, two individuals (Patients 4 and 6) initially clinically assessed as severe (Braun et al, 2020) clustered with patients that suffered from the mild form of COVID-19 ( Figure S1). Our results triggered a retrospective assessment, which revealed that patient 4 turned out to be suffering from type B influenza rather than a SARS-CoV-2 infection, whereas patient 6 was classified as severe due to recent R-CHOP chemotherapy, applied just ten days before his COVID-19-related hospitalisation.…”
Section: Rapid and Precise High-flow Rate Proteomics Identifies Novelmentioning
confidence: 99%
“…Sampling was performed as part of the Pa-COVID-19 study, a prospective observational cohort study assessing pathophysiology and clinical characteristics of patients with COVID-19 at Charité Universitätsmedizin Berlin (Braun et al, 2020) . All patients with SARS-CoV-2 infection proven by positive PCR from respiratory specimens and willing to provide written informed consent are eligible for inclusion.…”
Section: Clinical Samples Of Covid-19 Patientsmentioning
confidence: 99%
“…In fact, it was shown that patients recovered from COVID-19 developed virus neutralizing anti-S immunoglobulin (Ig) titers 7 . Given the requirement for T cell help in generation of high affinity IgG antibodies, this finding indicates that S-protein reactive T cell immunity was formed in those patients 8,9 . Accordingly, very recent studies identified SARS-CoV-2 S-protein reactive T cell responses in patients suffering from moderate, severe, and critical COVID-19 4,10 . Furthermore, it was shown that the amount of SARS-CoV-2 reactive T cells increased with disease progression 11 .…”
Section: Main Textmentioning
confidence: 99%